Analysis of the Factors Affecting Performance of Sustainable Supply Chain Management of Garut Arabica Coffee - Gagas Pragmawiguno; Alim Setiawan; Heti Mulyati (Jurnal Manajemen Bisnis, 2023)
Research aims: This study aims to analyze the factors influencing the sustainable supply chain management of Garut Arabica Coffee in increasing product competitiveness.Design/Methodology/Approach: This study used a quantitative approach with an exploratory and causal design to explain how one variable influences or is responsible for changes in other variables. A quantitative approach analyzed the factors influencing the sustainability of Garut Arabica Coffee’s supply chain operational performance.Research findings: Structural Equation Modeling (SEM) analysis revealed that economic, social, and environmental factors positively and significantly impacted the sustainability of the Garut Arabica Coffee supply chain. The SWOT analysis showed that it requires implementing an integrated strategy from all factors with the support of sustainable infrastructure facilities, programs to eradicate farmer poverty, recycling defective products, and monitoring suppliers using the ISO 140001 standard.Theoretical Contribution/Originality: This study analyzed the factors influencing the Garut Arabica Coffee sustainable supply chain and provides strategies based on supply chain sustainability indicators that can be implemented to overcome the problems faced.Practitioners/Policy Implications: This study gives beneficial information to stakeholders from farmers, cooperatives, and the government involved in developing the supply chain performance improvement of Garut Arabica Coffee production.Research Limitations/Implications: This research was still limited to the performance of the supply chain on a micro scale with 100 respondents, so the scope still needs to be expanded to have a bigger impact on society.